2016
DOI: 10.1589/jpts.28.2929
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between rounded shoulder posture, neck disability indices, and degree of forward head posture

Abstract: [Purpose] The present study aimed to examine the correlation between rounded shoulder posture, neck disability indices and the degree of forward head posture. [Subjects and Methods] Subjects aged 19–24 years were selected for this study, and the craniovertebral angle was used to measure the degree of forward head posture in the standing and seated positions. Vernier calipers were used to measure rounded shoulder posture in the supine position, and neck pain and functional disability were assessed using neck di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
1
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 19 publications
1
65
1
6
Order By: Relevance
“…This bending position exerts high pressure on the surrounding structures, including the muscles and joints of the neck. 7 The FHPs are common among dentists because they hold the neck and head in an unbalanced forward position to gain better visibility during dental procedures. This can result in a pain pattern that is often referred to as "tension neck syndrome."…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This bending position exerts high pressure on the surrounding structures, including the muscles and joints of the neck. 7 The FHPs are common among dentists because they hold the neck and head in an unbalanced forward position to gain better visibility during dental procedures. This can result in a pain pattern that is often referred to as "tension neck syndrome."…”
Section: Discussionmentioning
confidence: 99%
“…6 Furthermore, bad posture causes the head and shoulders to come forward, leading to FHP and rounded shoulders. 7 Although various studies have been carried out to determine the postural risk factors experienced by dentists, the authors are aware of only a few studies that discuss the possible relationship between MSP and posture; this study aimed to find the relation between MSP and vertebral deviations among male dentists in the UAE.…”
Section: 5005/jp-journals-10024-2335mentioning
confidence: 99%
“…In the study of Kim and Kim, their results showed no significant correlation was detected in standing and sitting position in CVA and RSP. (7) The limit of FHP was determined as <50°. (3) Kim and Kim were assessed rounded shoulder posture by height of acromion of dominant shoulder.…”
Section: Discussionmentioning
confidence: 99%
“…(3) Kim and Kim were assessed rounded shoulder posture by height of acromion of dominant shoulder. (7) Photography was utilized in this study to determine the shoulder angle rather than the supine position, to test the misalignments of corporal segments by photographic measurements of the sagittal postures of cervical spine and the shoulder. The photographic measurement of sagittal postures in the cervical spine and the shoulder is being increased in order to study misalignments on body parts, with several studies confirming that photogrammetry is highly reliable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation